New World: Harry Seidler, Brazil and the Australian City. Issue 1 (2nd January 2021) - Goad, Philip
ABSTRACT: In 1948, en-route to Australia from the United States, young Viennese-born architect Harry Seidler spent just over six weeks in Brazil. There, he worked briefly for Oscar Niemeyer and visited numerous examples of Brazilian modernism. Settling in Sydney, Seidler became one of Australia's foremost modernist architects. His output quickly shifted from deference to the work of his mentors Walter Gropius and Marcel Breuer to formal experiments determined by the peculiarities of Australia's geography and climate. He increasingly adapted elements that reflected his South American experiences. As his practice gained larger commissions, Seidler's engagement with the Australian city was similarly affected. His urbanism - as it developed - ran counter to the Australian city's Anglo-American trajectory that had shaped its form and character since the 1850s. This paper places Seidler's interests in Brazil within the Australian context, where Iberico-American modernism was known and understood but appeared in isolated examples with little or no urban reference. Seidler, instead, proposed a new vision for the Australian city, one that extended Giedion, Sert and Leger's wartime call for a new monumentality and combined architecture, art and landscape in a unified response: it was his answer to an urbanism for the New World.